1985
DOI: 10.1136/bmj.290.6476.1171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspirin on nasal resistance to airflow.

Abstract: The effect of aspirin on nasal resistance to airflow was investigated by rhinomanometry in 25 healthy subjects before and after ingestion of aspirin or vitamin C in a double blind crossover trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…No changes were observed in total nasal resistance after being exposed to ozone, sulfur dioxide, and smoking (8). In the studies conducted, it was demonstrated that aspirin resulted in a mild increase in the resistance, and antihistamines could increase the nasal resistance (9). Smoking, performing heavy exercise, and receiving medications such as antihistamines and corticosteroids were not recommended for subjects prior to the test.…”
Section: Discussionmentioning
confidence: 99%
“…No changes were observed in total nasal resistance after being exposed to ozone, sulfur dioxide, and smoking (8). In the studies conducted, it was demonstrated that aspirin resulted in a mild increase in the resistance, and antihistamines could increase the nasal resistance (9). Smoking, performing heavy exercise, and receiving medications such as antihistamines and corticosteroids were not recommended for subjects prior to the test.…”
Section: Discussionmentioning
confidence: 99%
“…There is no evidence that treatment with analgesics interferes with the natural recovery from URTI but there are reports that aspirin and paracetamol may increase the severity of the symptom of nasal obstruction associated with URTI. A single dose of 900 mg aspirin has been reported to cause an increase in nasal resistance to airflow in healthy volunteers (51) and there is one report that daily doses of 4000 mg aspirin and paracetamol caused nasal congestion when used by volunteers infected via rhinovirus challenge (48).…”
Section: Effe Cts On the Immune System And C Ourse Of Urtimentioning
confidence: 99%
“…Eccles et al 30 found that the nasal feeling of airflow, but not the resistance, is affected by inhaling menthol. Jones et al 31 reported a slightly increased nasal resistance, not accompanied by a corresponding feeling of obstruction, following aspirin use. The use of topical anesthetics on the nasal mucosa produces a feeling of nasal obstruction which is not accompanied by a decreased transnasal airflow.…”
Section: Discussionmentioning
confidence: 99%